Exploration of barriers and enablers for the use of the nutrition care process among a diverse sample of registered dietitian nutritionists: a mixed methods analysis - Asare, Irene A.; Papoutsakis, Constantina; Wright, Lauri; Colin, Casey (Frontiers in Nutrition, 2026)
BackgroundRegistered dietitian nutritionists (RDNs) use the Nutrition Care Process and its Terminology (NCP/T) to generate outcomes and demonstrate the impact of medical nutrition therapy. Despite integration into education in 2009, many RDNs continue to face challenges in its application.ObjectiveThis study aimed to identify barriers and enablers to NCP/T use to better understand how adoption can be improved, and to assess whether qualitative feedback from practicing RDNs aligns with quantitative findings from the 2017 International Nutrition Care Process and Terminology Implementation Survey (INIS).DesignAn explanatory sequential mixed-methods approach was used. Quantitative data was from United States based RDNs who participated in the 2017 INIS. The focus group discussion questions were informed by the INIS study and grounded in the Theory of Planned Behavior (13). Zoom technology (14) was used and all the discussions were audio recorded. Only participants and the interviewer were present on the call. Qualitative data from the focus group discussions included RDNs in clinical, community, and academic settings. Semantic thematic analysis was conducted to identify themes related to barriers and enablers to using NCP/T.Participants/settingINIS study recruitment utilized email lists, e-newsletters, and social media groups; responses from 4,426 active RDNs were analyzed. Focus group inclusion criterion was active RDNs based in the US; 38 RDNs participated in the focus groups.Statistical analyses performedCross-tabulation identified correlations between barriers/enablers and characteristics such as years of practice and practice setting (p < 0.05).ResultsINIS data showed an association between practice area, years of experience, and NCP/T use (p < 0.001). Enablers included peer support (59% of clinical RDNs, 60.3% of RDNs with 0–5 practice years) and job requirements (52.9% of clinical RDNs, 55.2% of those with 0–5 years). Barriers included limited time (28.9% of clinical RDNs, 29.4% with >16 years) and insufficient education (25% of clinical RDNs, 29.8% with >16 years). Focus groups identified additional enablers, such as integrating NCP/T into Electronic Health Records, and barriers, including eNCPT subscription access.ConclusionThe INIS study and focus groups revealed consistent barriers and enablers, underscoring the need for authoritative state-of-the-art training to address these factors and enhance NCP/T utilization.